A new species and records of Alepia Enderlein (Diptera, Psychodidae, Psychodinae) from Argentina - Omad, Guillermo Hugo (2012)
A new species of Neotropical Psychodidae, Alepia claritae sp. nov., is described from Argentina. Specimens were collected in a Malaise trap located in Misiones Province. Based on material from the same locality, we include a re-description of the adult male of Alepia copelata Quate (1999), previously known from Barro Colorado Island, Panama. These are the first records of Alepia and the sixth record of a Psychodinae species for the Neotropical region of Argentina.  A list of the non-phlebotomine Psychodidae for Argentina is included.